Workshop Perakitan Komputer Untuk Guru MI Mathla’ul Huda Cijantra - Eriyandi; Johan Wahyudi; Sabdo Purnomo; Toni; Suparlan (Politeknik Penerbangan Indonesia Curug, 2021)
The development of science at this time can hardly be separated from technology, especially information technology, therefore human resources who are involved in any field are required to be able to adapt to existing technological advances. In the world of education, the government has carried out many activities to improve the competence of teachers, one of which is by providing trainings on the use of information technology tools in education and teaching, which will later be applied in schools and other educational institutions. However, based on the reality around PPI Curug, there are still many schools with inadequate technological facilities and infrastructure, one of which is MI Mathla'ul Huda which is on Cijantra Jl. Gunung Batu Cijantra Village, Pagedangan Subdistrict, where some of the students are orphans and underprivileged. The problem arises when there is problem with the computer equipment used while the teachers' knowledge is still minimal. To overcome this problem MI was forced to pay extra for repairs and restoration, which of course became a burden for the school. Therefore, through community service activities this time it is aimed at providing education and training to teachers on how to assemble and install computer equipment. After attending education and training through workshops held by the Indonesian Aviation Polytechnic of Curug, the teachers already have the knowledge and skills to install and assemble computers so that when a problem occurs on a computer devices, it can be resolved by themselves, and teachers who are mostly honorary staff can get additional income with the knowledge they get during the workshop.